Desenvolvimento de biopolímeros de isolado proteico de soro de leite e nanofibra de celulose incorporados com óleo essencial de tomilho - Carvalho, Raissa Alvarenga (2016)
In this study, an active packaging was developed with whey protein isolate (WPI) and cellulose nanofiber (CNF) incorporated with thyme essential oil (TEO). The WPI was used as base polymer for the films, glycerol as a plasticizer, CNF as a reinforcing material and TEO as an antioxidant agent. In the first stage of the study, the best concentration of CNF was select based on the results obtained by the analysis of thickness, solubility, morphology (SEM), mechanical, permeability (WVP) and optical properties. In the second stage, the films were added with different concentrations of TEO and characterized as the morphological (SEM), thermal (DSC and TGA), structural (XRD and FTIR), mechanical, optical and WVP properties. In the last step, the antioxidant activities of TEO and active nanobiopolymers were evaluated and the application of the films in ground beef (Biceps femoris) was conducted in order to evaluate the ability of the active films in preventing the oxidation of meat by the analysis of TBA and color of the samples during storage at 4°C±1°C for 4 days. As results, the addition of the intermediate concentrations of CNF (2 and 4% w/w) allowed the formation of films more resistant to water, less permeable, more rigid and less flexible, with good dispersion of the nanoparticle along the polymer matrix. For the higher concentration of CNF (6% w/w), there was a tendency to agglomeration of nanoparticles by the polymer matrix, with maintenance of the properties analyzed. There was no difference in color and transparency of nanobiopolymers added with CNF. The addition of 4% (w/w) of CNF was selected for further studies and applications. The incorporation of different concentrations of TEO (20; 30 and 40% w/w) allowed the formation of films with good interaction between its components, high crystallinity index and increased the glass transition temperature (Tg) and thermal stability (TGA) with also a decreased in the permeability. The films were less yellow, with a tendency to green, paler and with less transparency with the addition of TEO. The mechanical properties were reduced and the dispersion of the CNF was decreased. The presence of the compounds thymol and carvacrol in TEO and nanobiopolymers added with the oil, were confirmed by gas cromatography, as well as its antioxidant activities through analysis of kidnapping free radicals DPPH and β-carotene/linoleic acid system. A decrease of the oxidation values was observed for ground beef samples aconditionated by nanobiopolymers added with TEO (TBA) and the treatment added with 20% (w/w) of TEO was able to maintain the red color of the meat shown by the results of color a*, saturation (C*) and hue angle (h*). The results indicated that the use of films with 4% (w/w) of CNF and 20% (w/w) of TEO was able to enhance film properties and prevent the oxidation of ground beef with a consequent maintenance of quality during the time and conditions studied.